Risk Factors for Obesity: A Systematic Review - Poniasih, Ami (Epidemiology and Society Health Review (ESHR), 2025)
Background: Obesity is excessive fat accumulation due to an imbalance between energy intake and energy use. Between 2010 and 2018, there was an increase in the prevalence of overweight (3.9% annual average) and obesity (8% yearly average) among adults aged over 18. This study aims to overview the factors associated with the incidence of obesity. Method: This systematic literature review generated the data using electronic sources: Google Scholar and PubMed. Articles were selected using keywords: risk factors, obesity, physical activity, and food intake. The inclusion criteria used were free full text published in Bahasa or English between 2018 and 2023. Exclusion criteria: Literature review articles and full text are not freely available. Results: The existence of a high-calorie consumption pattern can increase the incidence of obesity, and lack of physical activity can cause the accumulation of body fat, which contributes to obesity. The findings from this study can be used to determine risk factors for obesity. Conclusion: This systematic literature review article concludes that various factors are associated with obesity, including food intake, physical activity, and smoking.